Comparison of IVF Outcomes between Minimal Stimulation and High-Dose Stimulation for Patients with Poor Ovarian Reserve - Lazer, Tal; Dar, Shir; Shlush, Ekaterina; Al Kudmani, Basheer S.; Quach, Kevin; Sojecki, Agata; Glass, Karen; Sharma, Prati; Baratz, Ari; Librach, Clifford L. (International Journal of Reproductive Medicine, 2014)
We examined whether treatment with minimum-dose stimulation (MS) protocol enhances clinical pregnancy rates compared to high-dose stimulation (HS) protocol. A retrospective cohort study was performed comparing IVF and pregnancy outcomes between MS and HS gonadotropin-antagonist protocol for patients with poor ovarian reserve (POR). Inclusion criteria included patients with an anti-Müllerian hormone (AMH) ≤8 pmol/L and/or antral follicle count (AFC) ≤5 on days 2-3 of the cycle. Patients from 2008 exclusively had a HS protocol treatment, while patients in 2010 had treatment with a MS protocol exclusively. The MS protocol involved letrozole at 2.5 mg over 5 days, starting from day 2, overlapping with gonadotropins, starting from the third day of letrozole at 150 units daily. GnRH antagonist was introduced once one or more follicles reached 14 mm or larger. The HS group received gonadotropins (≥300 IU/day) throughout their antagonist cycle. Clinical pregnancy rate was significantly higher in the MS protocol compared to the HS protocol (P=0.007). Furthermore, the live birth rate was significantly higher in the MS group compare to the HS group (P=0.034). In conclusion, the MS IVF protocol is less expensive (lower gonadotropin dosage) and resulted in a higher clinical pregnancy rate and live birth rate than a HS protocol for poor responders.